Lani Phonological Interference in Indonesian Pronunciation - Tabuni, Onni; Nurhayani, Ika; Hamamah, Hamamah (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2020)
Papua is the eastern-most part of Indonesia, comprising the left half of the island of New Guinea. Lani is a group of people or tribe living in the mountains of Jayawijaya Papua, and they speak Lani language as their local language. The language used for formal purposes in Papua is Indonesian. However, many Lani people cannot speak Indonesian correctly. This study examined the phonological interference of Lani language on the spoken Indonesian of Lani native speakers in Malang. This research used descriptive qualitative with content analysis. The respondents were five native speakers of Lani living in Malang for less than a year. The 200 Swadesh wordlist (1971) was used to collect data of spoken Indonesian from the Lani native speakers to show the phonological interference of Lani on Indonesian. This research revealed two important findings: (1) the pronunciation of Indonesian words spoken by Lani native speakers was interfered with Lani phonological rules, in which the respondents tend to substitute the sounds of Indonesian which do not exist in Lani with Lani’s sounds, (2) the respondents intended to make the pronunciation of a second language (Indonesian) easier. This happened because they experienced difficulties in producing several phonemes of Indonesian not existing in Lani’s phonological system.